Fate of systemically and locally administered adipose-derived mesenchymal stromal cells and their effect on wound healing. (15th October 2019) - Kallmeyer, Karlien; André-Lévigne, Dominik; Baquié, Mathurin; Krause, Karl-Heinz; Pepper, Michael S.; Pittet-Cuénod, Brigitte; Modarressi, Ali
Abstract: There is increasing interest in the use of adipose-derived mesenchymal stromal cells (ASCs) for wound repair. As the fate of administered cells is still poorly defined, we aimed to establish the location, survival, and effect of ASCs when administered either systemically or locally during wound repair under physiological conditions. To determine the behavior of ASCs, a rat model with wounds on the dorsal aspect of the hind paws was used and two treatment modes were assessed: ASCs administered systemically into the tail vein or locally around the wound. ASCs were transduced to express both firefly luciferase (Fluc) and green fluorescent protein to enable tracking by bioluminescence imaging and immunohistological analysis. Systemically administered ASCs were detected in the lungs 3 hours after injection with a decrease in luminescent signal at 48 hours and signal disappearance from 72 hours. No ASCs were detected in the wound. Locally administered ASCs remained strongly detectable for 7 days at the injection site and became distributed within the wound bed as early as 24 hours post injection with a significant increase observed at 72 hours. Systemically administered ASCs were filtered out in the lungs, whereas ASCs administered locally remained and survived not only at the injection site but were also detected within the wound bed. Both treatments led to enhanced wound closure. It appears that systemically administered ASCs have the potential to enhance wound repair distally from their site of entrapment in the lungs whereas locally administered ASCs enhanced wound repair as they became redistributed within the wound bed. : Abstract : Adipose-derived mesenchymal stromal cells were administered either systemically or locally in a rat model of wound repair under physiological conditions. It appears that systemically administered adipose-derived mesenchymal stromal cells have the potential to enhance wound repair distally from their site of entrapment in the lungs whereas locally administered adipose-derived mesenchymal stromal cells enhanced wound repair as they became redistributed within the wound bed.